Microeconomics for MBAs : the economic way of thinking for managers - McKenzie, Richard B.; Lee, Dwight R. (Cambridge : Cambridge University Press, 2017)
Now in its third edition, this textbook develops the economic way of thinking through problems that MBA students will find relevant to their career goals. Theory and mathematics are kept as simple as possible and illustrated with real-life scenarios. The textbook package includes online video tutorials on key concepts and complex arguments, and topics likely to be assessed in exams. The distinguished author team has developed this textbook over twenty years of teaching microeconomics to MBA students. Chapters are clearly structured to support learning: Part I of each chapter develops key economic principles, whilst Part II draws on those principles to discuss organizational and incentive issues in management and focuses on solving the 'principal-agent' problem to maximize the profitability of the firm - lessons that can be applied to problems MBA students will face in the future. Economics and management are treated equally; this unique textbook presents economics as part of the everyday thinking of business people.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Microeconomics; Managerial economics